Performance enhancement of single-chamber sediment-microbial fuel cell with variation in cathode surface area - Teng, H.C.; Kok, B.C.; Uttraphan, C.; Yee, M.H. (GAZI University, 2020)
This study investigates the impact of cathode surface area on single chamber sediment-microbial fuel cell (S-MFC). A fixed graphite anode surface area of 0.000471m2 has been used on four S-MFCs coupled with four carbon fiber cloth cathode electrodes with variation of surface area. Pond sediment has been used as the anode medium that inoculated with acetate as substrate to ramp up the amount of electrochemical-active bacteria (EAB). The S-MFCs has been operated and monitored for 120 hours using Arduino based data logger. The outcomes of this observation period have indicated the S-MFC with larger cathode surface area (0.01m2) possess smaller internal resistance (123.96±2.68 Ω) and thus performed significantly better than other S-MFC with the smaller cathode surface area, resulting with average voltage and current of 0.598±0.008V and 4.827±0.124mA respectively, where a maximum power density of 2.867mW with a coulombic efficiency of 64.63% was achieved. Successful performance increase suggests enlargement of the cathode area could be the alternative to reduce the internal resistance in traditional MFCs for electricity generation.